Gene expression signature of human neuropathic pain identified through transcriptome analysis - Hu, Ling; Yin, Wei; Ma, Yao; Zhang, Qiushi; Xu, Qingbang (Frontiers in Genetics, 2023)
Neuropathic pain is a type of chronic pain that is characterized by ongoing discomfort and can be challenging to manage effectively. This study aimed to identify genes associated with neuropathic pain through transcriptome analysis in order to gain a better understanding of the mechanisms underlying this chronic, difficult-to-treat pain. We conducted transcriptome analysis using a training dataset of 202 individuals, including patients with neuropathic pain and healthy controls. Our analysis identified five genes (GTF2H2, KLHL5, LRRC37A4P, PRR24, and MRPL23) that were significantly differentially expressed in the tissue of patients with neuropathic pain compared to controls. We constructed a neuropathic pain signature using these five genes and validated it using an independent dataset of 25 individuals. Receiver operating characteristic (ROC) curve analysis demonstrated that this signature had a high level of accuracy in differentiating between neuropathic pain patients and healthy controls, with an area under the curve (AUC) of 0.83 [95% CI 0.65-1]. These findings suggest that these five genes may be potential therapeutic targets for neuropathic pain